SEJARAH PERKEMBANGAN PENDIDIKAN TASAWUF (Studi Atas Tariqah Qadiriyah wa Naqsabandiyah di Kudus Jawa Tengah) - Mu'min, Ma'mun (Pascasarjana IAIN Kudus, 2016)
This paper is a summary of the results of my thesis research at the Faculty of Humanities Postgraduate Program at Diponegoro University by 2013 and then it was developed, particularly on the data that is more up to date. The main purpose of writing this article is to examine the history of the Sufism education, with focus on the education development history of Thariqat Qadiriyah wa Naqsyabandiyah in Piji Kudus. This research used the historical method and phenomenological approach of Edmund Husserl to understand the meaning of education development history of the Thariqat Qadiriyah wa Naqsyabandiyah in Piji Kudus and the Sufism ideas of Kyai Haji Muhammad Siddiq as a Murshid of the Thariqat Qadiriyah wa Naqsyabandiyah in Piji Kudus. This research reveals the mysticism education and Sufism thought development of Kyai Siddiq in Piji Kudus. Some of the research results that can be described in this paper are: first, the education development of Thariqat Qadiriyah wa Naqsyabandiyah Piji Kudus begins with the formation of a small mosque which was built in 1837 on the initiative of Mantri Sutowijoyo (1835-1870), in 1920 was developed into al-Aqsa Mosque as of now. Second, in 1956 Kyai Siddiq built an Islamic primary school, in 1970 built an Islamic Junior High School, in 1972 established an Islamic Boarding School of Manba'ul Falah, and in 2009 established a vocational education. Third, in 1972 Kyai Shiddiq established Thariqat Qadiriyah wa Naqsyabandiyah Piji Kudus after doing a bai'at for Murshid of the Thariqat Qadiriyah wa Naqsyabandiyah Rejoso Peterongan Jombang, Kyai Haji Tamim Romli. Fourth, the education institution that taught by Kyai Siddiq, namely tawheed education (monotheism), Sharia (Shari'ah), thariqat (congregations) and ma'rifat. Fifth, after the death of Kyai Siddiq (2011) Thariqat Qadiriyah wa Naqsyabandiyah Piji Kudus led by Kyai Haji Abdul Latif Siddiq, Kyai Haji Affandi Siddiq, and Kyai Haji Siddiq Muchtar Amin.